3D simulations of disc winds extending radially self-similar MHD models - Stute, Matthias; Gracia, José; Vlahakis, Nektarios; Tsinganos, Kanaris; Mignone, Andrea; Massaglia, Silvano (OUP, 2014)
Disc winds originating from the inner parts of accretion discs are considered as the basic component of magnetically collimated outflows. The only available analytical magnetohydrodynamic (MHD) solutions to describe disc-driven jets are those characterized by the symmetry of radial self-similarity. However, radially self-similar MHD jet models, in general, have three geometrical shortcomings: (i) a singularity at the jet axis, (ii) the necessary assumption of axisymmetry and (iii) the non-existence of an intrinsic radial scale, i.e. the jets formally extend to radial infinity. Hence, numerical simulations are necessary to extend the analytical solutions towards the axis, by solving the full three-dimensional equations of MHD and impose a termination radius at finite radial distance. We focus here on studying the effects of relaxing the (ii) assumption of axisymmetry, i.e. of performing full 3D numerical simulations of a disc wind crossing all MHD critical surfaces. We compare the results of these runs with previous axisymmetric 2.5D simulations. The structure of the flow in all simulations shows strong similarities. The 3D runs reach a steady state and stay close to axisymmetry for most of the physical quantities, except for the poloidal magnetic field and the toroidal velocity which slightly deviate from axisymmetry. The latter quantities show signs of instabilities, which, however, are confined to the region inside the fast magnetosonic separatrix surface. The forces present in the flow, both of collimating and accelerating nature, are in good agreement in both the 2.5D and the 3D runs. We conclude that the analytical solution behaves well also after relaxing the basic assumption of axisymmetry.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; Astrophysics - Solar and Stellar Astrophysics; ISM: jets and outflow; methods: numerical; MHD; stars: formation; stars: pre-main-sequence